2002
DOI: 10.1007/s11908-002-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology and treatment of Candida sepsis

Abstract: Sepsis can occur during disseminated candidiasis, but its pathogenesis differs from that caused by typical prokaryotic pathogens. Complex interactions between defects in host defense and "relative" virulence factors expressed by Candida lead to dissemination of the saprophyte to parenchymal organs, and subsequently to onset of multiorgan failure. This review focuses first on the pathophysiology of Candida sepsis, detailing current understanding of host-pathogen interactions. We then consider the choice of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 119 publications
(80 reference statements)
0
23
0
1
Order By: Relevance
“…First, if the majority of the cytokines detected in the whole-organ analysis were of serum origin, similar profiles would have been detected in the kidney and in the highly vascularized spleen. Furthermore, investigators have found that serum levels of inflammatory cytokines are low during lethal disseminated candidiasis (2,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, if the majority of the cytokines detected in the whole-organ analysis were of serum origin, similar profiles would have been detected in the kidney and in the highly vascularized spleen. Furthermore, investigators have found that serum levels of inflammatory cytokines are low during lethal disseminated candidiasis (2,33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a type 1 immune response is protective against both disseminated and mucocutaneous candidiasis, while a dominant type 2 immune response results in increased susceptibility to disseminated disease (6,10,17,28,30). Furthermore, during Candida sepsis there is a down-regulation of the host response to the fungus (33), suggesting that T-regulatory (Treg) or Th3 cells, which predominantly secrete the immunosuppressive cytokines IL-10 and transforming growth factor beta (TGF-␤) (8,9,11), regulate host immunity to high inoculum levels of Candida. This notion is supported by data from Romani's group, who recently reported that C. albicans induces IL-10 ϩ /TGF-␤ ϩ Treg cells that mediate oral tolerance following intragastric infection (19).…”
mentioning
confidence: 99%
“…Invasive candidiasis, caused mainly by Candida albicans and also by other Candida species, has emerged as a major cause of morbidity and mortality in immunocompromised host, and Candida species represent one of the most common nosocomial bloodstream isolates (Calderone 2002;Spellberg and Edwards 2002). These species are present as commensal organisms, but when the normal host defence is impaired, they act as serious agents of infection, and are considered as opportunistic pathogens of humans.…”
Section: Introductionmentioning
confidence: 99%
“…The major clinical risk factors for developing disseminated candidiasis have been well described (58). These key risk factors include colonization with the organism, gastrointestinal or cardiac surgery, a prolonged stay in an intensive care unit, burns, and use of central venous catheters, broad-spectrum antibiotics, and parenteral nutrition.…”
mentioning
confidence: 99%